Molecular phylogeny and systematics of spider wasps (Hymenoptera: Pompilidae): redefining subfamily boundaries and the origin of the family. (October 2015) - Waichert, Cecilia; Rodriguez, Juanita; Wasbauer, Marius S.; von Dohlen, Carol D.; Pitts, James P.
<x xml:space="preserve">Abstract</x> Spider wasps (Hymenoptera: Pompilidae) constitute a monophyletic family supported by numerous morphological and behavioural traits. The subfamilial and tribal classifications, however, have a history of conflicting and confusing designations and nomenclature. Here, we reconstruct a molecular phylogeny of Pompilidae from Bayesian and maximum‐likelihood analyses of four nuclear molecular markers (elongation factor‐1 α F2 copy, long‐wavelength rhodopsin, RNA polymerase II, and 28S ribosomal RNA). A Bayesian divergence‐time estimation analysis was performed using four calibration points and an ancestral‐area reconstruction was performed with a Bayesian binary Markov chain Monte Carlo method. New relationships are recovered, and new subfamilial delimitations are proposed and discussed based on the phylogeny. The origin of Pompilidae was c. 43.3 Mya, probably in the Nearctic region. Most of the extant subfamilies originated from the late Eocene to the Oligocene, and their current distributions are the product of various dispersal events that occurred over the course of ∼40 Mya. This is the first phylogenetic reconstruction of Pompilidae from molecular characters, with broad geographical and taxonomic sampling. The following subfamilies and relationships are recognized: Ctenocerinae + ((Ceropalinae + Notocyphinae) + (Pompilinae + Pepsinae)). We revalidate Notocyphinae, which contains only Notocyphus, and define a new tribe in Pompilinae: Sericopompilini. Priochilini is reinstated. Sericopompilini contains Sericopompilus as the sole representative; Priochilini contains Priochilus and Balboana. Epipompilus and Chirodamus are now classified as Pepsinae. © 2015 The Linnean Society of London